RBBP4 modulates gene activity through acetylation and methylation of histone H3 lysine 27 - Mu, Weipeng; Murcia, Noel S; Smith, Keriayn N.; Menon, Debashish U; Yee, Della; Magnuson, Terry (bioRxiv, 2021)
RBBP4 is a core subunit of polycomb repressive complex 2 (PRC2) and HDAC1/2-containing complexes, which are responsible for histone H3 lysine 27 (H3K27) methylation and deacetylation respectively. However, the mechanisms by which RBBP4 modulates the functions of these complexes remain largely unknown. We generated viable mouse embryonic stem cell lines with RBBP4 mutations that disturbed methylation and acetylation of H3K27 on target chromatin and found that RBBP4 is required for PRC2 assembly and H3K27me3 establishment on target chromatin. Moreover, in the absence of EED and SUZ12, RBBP4 maintained chromatin binding on PRC2 loci, suggesting that the pre-existence of RBBP4 on nucleosomes serves to recruit PRC2 to restore H3K27me3 on newly synthesized histones. As such, disruption of RBBP4 function led to dramatic changes in transcriptional profiles. In spite of the PRC2 association, we found that transcriptional changes were more closely tied to the deregulation of H3K27ac rather than H3K27me3 where increased levels of H3K27ac were found on numerous cis-regulatory elements, especially putative enhancers. These data suggest that RBBP4 controls acetylation levels by adjusting the activity of HDAC complexes. As histone methylation and acetylation have been implicated in cancer and neural disease, RBBP4 could serve as a potential target for disease treatment.